2012
DOI: 10.1002/jbm.a.34391
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate glass improves angiogenesis capacity of poly(lactic acid) scaffolds and stimulates differentiation of adipose tissue‐derived mesenchymal stromal cells to the endothelial lineage

Abstract: The angiogenic capacity of a new biomaterial composite of poly(lactic acid) and calcium phosphate glass (PLA/CaP) was analyzed by noninvasive bioluminescence imaging (BLI) and histological procedures. Human adipose tissue-derived mesenchymal stromal cells expressing cytomegalovirus (CMV) promoter regulated Photinus pyralis luciferase (hAMSC-PLuc) grew up to 30 times the initial cell load, in vitro, when seeded in PLA/CaP scaffolds, but suffered an initial growth crisis followed by recovery when the scaffolds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…19 It has been demonstrated that the presence of G5 glass particles not only increases cell attachment and spreading but also triggers angiogenesis and bone formation owing the Ca 2+ release and stiffness of the glass. 22,23 Indeed, several studies have demonstrated the relevant role of ions on tissue regeneration. 24,25 Given that the glass particles incorporated into the polymer scaffold are partially exposed in the surface, as demonstrated by an alizarin red assay (where only the calcified inorganic phase is stained in red color, Fig.…”
Section: Design and Architecture Of 3d Scaffoldsmentioning
confidence: 99%
“…19 It has been demonstrated that the presence of G5 glass particles not only increases cell attachment and spreading but also triggers angiogenesis and bone formation owing the Ca 2+ release and stiffness of the glass. 22,23 Indeed, several studies have demonstrated the relevant role of ions on tissue regeneration. 24,25 Given that the glass particles incorporated into the polymer scaffold are partially exposed in the surface, as demonstrated by an alizarin red assay (where only the calcified inorganic phase is stained in red color, Fig.…”
Section: Design and Architecture Of 3d Scaffoldsmentioning
confidence: 99%
“…Two hypotheses can thus be drawn: either stromal cells are able to differentiate into endothelial cells or endothelial cells are recruited to the grafting site by stromal cells. Both scenarios have already been described [33][34][35][36], and we believe these phenomena may contribute to the development of new ovarian tissue, as blood vessels containing red blood cells, a sign of normal functioning, were also seen within the alginate matrix after only 1 week of grafting. Moreover, the number of vessels per surface unit was also similar to our previous study [12], in which more endothelial cells were grafted.…”
Section: Discussionmentioning
confidence: 87%
“…As another representative example, the angiogenic capacity of adipose‐derived stromal cells (ADSCs) was significantly enhanced when seeded in poly(lactic acid) and calcium phosphate glass (PLA/CaP) scaffold through colonization by isolectin B 4 ‐positive host endothelial cells, which was evidenced by formation of functionally connected vascular structures enabling blood perfusion ( Figure 1 ). The colonization process was promoted by cell‐scaffold interactions in response to matrix remodeling enzymes released from embedded ADSCs during regeneration progresses.…”
Section: Type Of Polymers and Design Strategiesmentioning
confidence: 99%
“…* p < 0.05 according to Student's t test; AU, arbitrary units. Reproduced with permission . Copyright 2013, John Wiley and Sons.…”
Section: Type Of Polymers and Design Strategiesmentioning
confidence: 99%